(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The legal framework, normative legal acts of the order and regulations regulating the management of solid domestic waste in Ukraine, and the activities of executive bodies and local self-government bodies in this area are analyzed. The order of dealing with solid household waste and the problems that are facing today. The magnitude of the impact and future trends. It is concluded that there is no clear organizational structure of waste management in central and local government in Ukraine, there is no proper control over observance of the legislative and norms of emissions and management of solid domestic waste. The process of implementation of the Ukrainian legislation in the field of waste management to the EU legislation and the problems of their introduction and future prospects, which partially solve the problems of waste management in Ukraine, are revealed.